Bituminous mixtures in road construction - Hunter, Robert N. (Thomas Telford, 1994)
Addresses the theoretical and practical aspects of the design manufacture, and laying of bituminous mixtures. This book provides information on materials specification, test methods and harmonisation of standards, and is useful for engineers working on the construction and maintenance of highways.
Keywords: Pavements, Bituminous.; Pavements, Asphalt.; Bituminous materials.; Road materials.; elektronické knihy; electronic books